Party Switching in Israel A Historical and Comparative Analysis. - Nikolenyi, Csaba (State University of New York Press, 2023)
Analyzes the history of legislative party switching and its regulation in the Israeli Knesset.
Description based upon print version of record.
Ninth Knesset
Keywords: Israel. -- Keneset -- Rules and practice.; Israel. -- Keneset; Party affiliation -- Israel.; Political parties -- Israel.; Political candidates -- Israel.; Partis politiques -- Adhésion -- Israël.; Candidats (Élections) -- Israël.; POLITICAL SCIENCE / Comparative Politics.; Party affiliation; Political candidates; Political parties; Israel; Rules